Seroprevalence, Risk Factors, and Rodent Reservoirs of Leptospirosis in an Urban Community of Puerto Rico, 2015 - Briskin, Emily A.; Casanovas-Massana, Arnau; Ryff, Kyle R.; Morales-Estrada, Shirley; Hamond, Camila; Perez-Rodriguez, Nicole M.; Benavidez, Kathryn M.; Weinberger, Daniel M.; Castro-Arellano, Iván; Wunder, Elsio A.; Sharp, Tyler M.; Rivera-Garcia, Brenda; et al. (The Journal of infectious diseases, 2019)
The burden of leptospirosis in Puerto Rico remains unclear due to underreporting. A cross-sectional survey and rodent trapping was performed in a community within San Juan, Puerto Rico to determine the seroprevalence and risk factors for Leptospira infection. The microscopic agglutination test was used to detect anti-Leptospira antibodies as a marker of previous infection. We evaluated Leptospira carriage by quantitative polymerase chain reaction among rodents trapped at the community site. Of 202 study participants, 55 (27.2%) had Leptospira agglutinating antibodies. Among the 55 seropositive individuals, antibodies were directed most frequently against serogroups Icterohaemorrhagiae (22.0%) and Autumnalis (10.6%). Of 18 captured rodents, 11 (61.1%) carried pathogenic Leptospira (Leptospira borgpetersenii, 7 and Leptospira interrogans, 2). Four participants showed their highest titer against an isolate obtained from a rodent (serogroup Ballum). Increasing household distance to the canal that runs through the community was associated with decreased risk of infection (odds ratio = 0.934 per 10-meter increase; 95% confidence interval, .952-.992). There are high levels of Leptospira exposure in an urban setting in Puerto Rico, for which rodents may be an important reservoir for transmission. Our findings indicate that prevention should focus on mitigating risk posed by infrastructure deficiencies such as the canal.